Rooted cosmopolitans : Jews and human rights in the twentieth century - Loeffler, James Benjamin (Yale University Press, 2018)
"A stunningly original look at the forgotten Jewish political roots of contemporary international human rights, told through the moving stories of five key activists The year 2018 marks the seventieth anniversary of two momentous events in twentieth-century history: the birth of the State of Israel and the creation of the Universal Declaration of Human Rights. Both remained tied together in the ongoing debates about the Israeli-Palestinian conflict. Yet the surprising connections between Zionism and the origins of international human rights are completely unknown today. In this riveting account, James Loeffler explores this controversial history through the stories of five remarkable Jewish founders of international human rights, following them from the prewar shtetls of eastern Europe to the postwar United Nations, a journey that includes the Nuremberg and Eichmann trials, the founding of Amnesty International, and the UN resolution of 1975 labeling Zionism as racism. The result is a book that challenges long-held assumptions about the history of human rights and offers a startlingly new perspective on the roots of the Israeli-Palestinian conflict."--